Annual Plan 1968-69 Volume I Memoranda Jammu and Kashmir State - Planning Commission (Planning Commission, 1967)
For this subhead which consists of various Programme an outlay of Rs.9.20 cores has been earmarked in the state IV Plan. During the year 1966-67 which was the first year of the IV Plan an outlay of Rs. 126.38 lakhs was budgeted against which actual utilization has been of the order of Rs. 72.41 laces. For the current year an outlay of Rs.175 lakhs was approved by the Planning Commission which was also budgeted. The anticipated lakhs Expenditure for the year is expected to be Rs 16 which accounts for a satisfactory performance for the year. For the next year an outlay of Rs. 215.60 lakhs has proposed in the draft annual plan This means a step up of Rs. 40.60 lakhs over the current years budgeted outlay.
Government of Jammu and Kashmir
Planning Department
Keywords: Agricultural Production; Forestry; Soil conservation; Animal Husbandry; Statistics; Information; Publicity; Local Bodies; Printing Press; Metric System of Weights; Measure; Development of Hill; Development of backward areas; Intensive order; Development Blocks; Dairying; Milk supply